Spectrophotometricaly Evaluation of Probiotic Growth in Liquid Media - HOMAYOUNI, AZIZ; REZA EHSANI, MOHAMAD; AZIZI, ASLAN; HADI RAZAVI, SEYED; SAIED YARMAND, MOHAMAD (Asian Journal of Chemistry, 2010)
A completely randomized design experiment was applied in triplicates to evaluate the survival of four probiotic strains in liquid media. The growth and survival rate of these probiotic strains (Lactobacillus acidophilus, Lactobacillus casei, Bifidobacterium lactis and Bifidobacterium longum) in varying amount of sucrose (10, 15, 20 and 25 %), oxygen scavengering components (0.05 % L-cysteine and 0.05 % L-ascorbate) and temperatures (4 and -20 °C) during different periods of time (1, 2 and 3 months) were evaluated in MRS-broth medium. Optical density at 580 nm wavelength was used to measure growth. Lactobacilli strains proved to be highly resistant in comparison with Biffidobacteria strains. Growth and survival rate of Lactobacillus casei showed to be the highest. Spectrophotometricaly measurement of optical density at 580 nm was showed to be the simple, rapid and inexpensive method for evaluation of probiotic growth.